ANALISIS SISTEM AKUNTANSI INSTANSI PADA KANTOR PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI UTARA - Worung, Yefie Ignasia; Morasa, Jenny; Tinangon, Jantje (Universitas Sam Ratulangi, 2015)
The central government is a party that is given the responsibility and rights to run the government systems, and social services to the society. In order to fulfill these duties, central government needs a system that can assist the government in carrying out its functions. Accounting Institution System is one embodiment of the systems of government that regulate the flow of goods, services and funds into supporting the implementation of the government's job. The purpose of this study is to analyze the suitability of the SAI management system procedures and regulations, analyze the course of the reconciliation process, and analyze the use of information systems related to Accounting Institution System on BKKBN SULUT. The analytical method used is descriptive comparative method which is a method for finding answers fundamentally about causation by analyzing factors of occurrence or the appearance of certain phenomena. The results showed that the organizational structure has described the separation of responsibilities and authority, especially the things related to the SAI that consist of SAK and SIMAK-BMN, the implementation of the SAI in BKKBN SULUT has not been fully implemented in accordance with applicable regulations, both internal and external reconciliation generally been accomplished by the procedure and only experienced by technical errors, while the information relating to the SAI system has been implemented properly and structured.